INTEGRATED DIGITAL LAUNDRY APPLICATION FOR MSMES: END-TO-END OPERATIONS AND REMOTE MONITORING - Joharini; Kursehi Falgenti; Intan Saesaria; Hanief Fathul Bahri Ahmad; Mohamad Prastya (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs), particularly in service sectors such as laundry businesses, often rely on fragmented and manual operational practices, resulting in inefficiencies and limited managerial visibility. Existing digital laundry applications typically support isolated functionalities and lack end-to-end integration. This study proposes and evaluates an integrated digital laundry application that supports end-to-end operations and remote business monitoring for MSMEs. The research adopts a Design Science Research (DSR) approach combined with Agile-based development. A functional prototype was implemented using Flutter-based mobile applications for customers and staff, along with a web-based dashboard for business owners. The system integrates customer booking, operational workflows, digital payments, automated financial recording, and real-time monitoring within a unified platform. Evaluation was conducted through functional testing, System Usability Scale (SUS) assessment, and business impact analysis involving 10 participants. The system achieved a SUS score of 78.5, indicating good usability. In addition, transaction errors were reduced by approximately 70%, and service processing time improved by 47%. These results demonstrate that the proposed system enhances operational efficiency, financial transparency, and managerial control. This study contributes an empirically validated, domain-specific digital artifact that operationalizes digital transformation and technopreneurship concepts in MSMEs